The effects of the SARS-CoV-2 pandemic on children and youth with special health care needs - Michaud, Mel; Dietz, Irene Cihon (Frontiers in Pediatrics, 2023)
This article seeks to review the current knowledge of the SARS-CoV-2 (Covid 19) virus and the health effects for CYSHCN. Recognition of the disease could be difficult, as symptoms in children ae at times different than adults and can mimic other common childhood viral infections. Children with underlying medical conditions did make up a higher proportion of those hospitalized, but also were affected in other ways including loss of nursing supports, missed education and rehabilitative services, and increased stress for the families, affecting mental health in this vulnerable population. This review seeks to address what is currently known about the overall effects on Children and youth with special health care needs (CYSHCN) and their families. Ongoing analysis of large national and international data sets, as well as smaller reports based on local resources, and family resilience is necessary.